Analisis Tindak Tutur Direktif dalam Film (Generasi Micin vs Kevin) - Bidya Astara; Trisfayani Trisfayani; Ririn Rahayu (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to describe the directive speech acts contained in the movie “Generasi Micin vs Kevin” directed by Fajar Nugros. The method used in this research is qualitative method. The data collection techniques used in this research are listening technique, recording technique, and note-taking technique. The data in this study are sentences in the dialog spoken by the characters in the film “Generasi Micin vs Kevin” which contains directive speech acts. The data source in this research is the movie “Generasi Micin vs Kevin”. Based on the results of research and discussion of directive speech acts in the movie “Generasi Micin vs Kevin”, 8 types of directive speech acts were found, namely: requesting, allowing, commanding, prohibiting, asking, pleading, advising, and recommending. Of the 8 types of directive speech acts, the most data is asking and the least data is pleading. The movie “Generasi Micin vs Kevin” belongs to the teen comedy drama genre. This is reason why the most asking data is found in this study.